Handbook on gender in Asia - Huang, Shirlena; Ruwanpura, Kanchana N. (International Handbooks on Gender, 2020)
"Exploring gender as a fundamental factor in the way that lives of individuals, families and societies across Asia are organized, this timely Handbook studies the importance of modernization and globalization for understanding gender in Asia. It brings together a wide range of scholarly perspectives on five critical areas in the field: ageing and health; labour; migrations and mobilities; gender at the margins, and the theory and practice of researching in Asia. Using empirical case studies, contributors highlight the challenges and changes to cultured traditions and practices that surround gendered norms surrounding the societal roles of men and women in Asia. Identifying gaps in current research, and using both qualitative and quantitative methods to explore the topic, this volume demonstrates the difference a gendered perspective makes in providing a better understanding of these issues in Asia. It offers fresh, nuanced insights to socio-political currents in Asian countries. This far-reaching collection will be an essential read for scholars in the social sciences interested in gender issues in Asia, Asian geography, human geography and gender politics; and for NGOs and policy makers"--Provided by publisher.